Significant Reductions in Posttraumatic Stress Symptoms in Congolese Refugees Within 10 days of Transcendental Meditation Practice. Issue 1 (10th February 2014) - Rees, Brian; Travis, Fred; Shapiro, David; Chant, Ruth
Abstract: This follow‐up pilot study tested whether Transcendental Meditation® (TM) practice would significantly reduce symptoms of posttraumatic stress in Congolese refugees within 10 days after instruction. The Posttraumatic Stress Disorder Checklist–Civilian (PCL‐C) was administered to nonmatched waitlist controls from a previous study 3 times over a 90‐day period. Within 8 days of the third baseline measure, 11 refugees were taught TM, then retested 10 days and 30 days after instruction. Average PCL‐C scores dropped 29.9 points from 77.9 to 48.0 in 10 days, then dropped another 12.7 points to 35.3 at 30 days. Effect size at 10 days was high ( d = 4.05). There were no adverse events. All participants completed the study and were able to practice TM.